Vascular endothelial growth factor in systemic lupus erythematosus in correlations with disease activity and nailfold capillaroscopic changes - Sherin M.H Hamza; Nermeen S. Khalil; Rasha M Hamoda; Marwa A El-Asfahani (SpringerOpen, 2019)
Background Angiogenesis plays a role in the pathogenesis of systemic lupus erythematosus (SLE). Both serum vascular endothelial growth factor (VEGF) and capillaroscopic abnormalities may reflect intensity of microcirculatory changes in the course of SLE. Aims To quantify serum VEGF level and its correlation with microvascular changes, assessed by nailfold capillaroscopy (NFC), and possible relationship with SLE activity. Patients and methods A total of 90 patients with SLE were subjected to detailed medical history and clinical examination and assessment of disease activity using the SLE Disease Activity Index score and organ damage using Systemic Lupus International Collaborating Clinics/American College of Rheumatology damage index. Laboratory investigations were done including autoantibodies [anti-nuclear antibody, anti-DNA, anti-cardiolipin (immunoglobulin G and immunoglobulin M), and lupus anticoagulant]. VEGF serum level was measured using enzyme-linked immunosorbent assay. NFC examination was done for recognition of NFC abnormalities. Results Serum VEGF level was elevated in the entire study group (mean of 831±572 ng/l), with a statistically highly significant correlation with Systemic Lupus International Collaborating Clinics/American College of Rheumatology damage index and SLE Disease Activity Index score of disease activity (r=0.349, P=0.001, and r=0.897, P<0.001, respectively), together with a significant positive correlation with the presence of nephritis (P=0.002), positive anti-double-stranded DNA (P≤0.001), and consumed C3 and C4 (P≤0.001), which are laboratory markers indicating lupus activity. Moreover, a higher serum VEGF level was associated with severe NFC changes with a statistically highly significant positive correlation with the capillary width (r=0.561, P<0.001), capillary length (r=0.411, P<0.001), and mean capillary density (r=0.308, P=0.003). Conclusion Increased serum VEGF level and progression of NFC score had been directly related to lupus activity and internal organ involvement, especially nephritis.